2020
DOI: 10.26434/chemrxiv.12309755.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Poly(alkylene 2,5-Furanoate)s Thin Films: Morphology, Crystallinity and Nanomechanical Properties

Abstract: Poly(alkylene 2,5-furanoate)s are considered as the most attractive and interesting alternatives to replace oil-based terephthalic polymers. These furan-based polyesters can be synthesized using fully bio-based synthetic strategies, allowing to reduce the environmental impact of plastics. At the same time, these polymers have shown outstanding thermal, mechanical and gas-barrier properties. All these results envisage their industrial use in the near future. Now, considering the downscaling of the products’ siz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This result is in line with previous works where PTF, PBF, and PHF showed a cold crystallization [24,28,[31][32][33], while PPeF remained in an amorphous state regardless of the thermal treatments [26,31,32]. In fact, this particular material only showed crystallization after being stored at room temperature for over 6 months [39,40]. On the contrary, in the case of SL samples, the melt crystallization occurring while slowly cooling showed an odd/even effect.…”
Section: Segmental Relaxationsupporting
confidence: 91%
“…This result is in line with previous works where PTF, PBF, and PHF showed a cold crystallization [24,28,[31][32][33], while PPeF remained in an amorphous state regardless of the thermal treatments [26,31,32]. In fact, this particular material only showed crystallization after being stored at room temperature for over 6 months [39,40]. On the contrary, in the case of SL samples, the melt crystallization occurring while slowly cooling showed an odd/even effect.…”
Section: Segmental Relaxationsupporting
confidence: 91%
“…This result is in line with recent AFM observations of PPeF crystallization in thin film geometry, where crystalline structures started appearing after 3 months of storage at room temperature. 55 To provide further information about the crystallization behavior of bulk PPeF, in our current work we performed DSC and XRD studies of a freshly prepared sample as a function of the storage time, as presented in Figure S1. There, it is observed that the PPeF film requires about 4 months to develop some detectable crystalline structures.…”
Section: Discussionmentioning
confidence: 99%
“…23,25 Specifically, the different number of methylene groups has a direct effect on the chain mobility and crystallizing capability. 23,[55][56] These characteristics allow to obtain from amorphous to semicrystalline polymers, which at room temperature can be in the glassy or in the rubbery state. According to these features, a different microstructure can develop, having a direct effect on the macroscopic properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations